THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE WORK PRODUCTIVITY AT ULAKAN PUBLIC HEALTH CENTER, PADANG PARIAMAN DISTRICT - Salfadri, Salfadri; Susi Yuliastanti; Utama Putra Jaya (Journal of Social and Economics Research, 2025)
This study aims to determine and analyze the influence of leadership style and work motivation on employee work productivity at the UPTD Ulakan Health Center, Padang Pariaman Regency. The population in this study amounted to 44 people who are employees of the UPTD Ulakan Health Center, Padang Pariaman Regency, and the sample in this study was 34 people, where the method for determining the number of samples used was purposive sampling. Data collection was carried out using a questionnaire. The analysis method used was multiple regression analysis. The data analysis method was Multiple Linear Regression, while the hypothesis testing method was the t-test and F-test. The results of this study indicate that: the leadership style variable partially had a positive and significant effect on employee work productivity at the UPTD Ulakan Health Center, Padang Pariaman Regency, while the work motivation variable partially had a negative and insignificant effect on employee work productivity at the UPTD Ulakan Health Center, Padang Pariaman Regency. Simultaneously, the leadership style and work motivation variables had a significant effect on employee work productivity at the UPTD Ulakan Health Center, Padang Pariaman Regency.